2019
DOI: 10.1530/ec-19-0088
|View full text |Cite
|
Sign up to set email alerts
|

Association between isolated hypothyroxinaemia in early pregnancy and perinatal outcomes

Abstract: Background The effect of isolated maternal hypothyroxinaemia (IMH) on pregnancy complications and neonatal outcomes in human beings is still controversial. Methods This was a retrospective cohort study based on the electronic medical register system. The records of women with a singleton pregnancy who sought antenatal examination between January 2014 and December 2015 at Shanghai First Maternity and Infant Hospital were extracted from the electronic medical records system. Thyroid-stimulating hormone (TSH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
“…Nine studies investigated the association of maternal IMH and gestational HTN, preeclampsia and eclampsia (6,11,14,16,20,(23)(24)(25)28). Neither preeclampsia nor eclampsia were associated with IMH diagnosed in rst or second trimesters of pregnancy; in addition, all the above studies except for two (6,11) found no signi cant association between maternal IMH and gestational HTN. Gong et al (2019) however reported that IMH identi ed in the second trimester was associated with increased risk of only gestational HTN, particularly among women with BMI < 25 kg/m 2 , (adjusted OR: 4.2, 95% CI: 1.61-10.96) (6).…”
Section: Feto-maternal Outcomesmentioning
confidence: 99%
See 3 more Smart Citations